La lutte internationale contre le réchauffement climatique comme étant une source de dégradation des ressources marines - Syrine Ismaili (Études Caribéennes)
Marine resources are a wealth of great economic importance for many countries in the world. Due to the action of man, these resources undergo embrittlement and rarification among others to pollution, overfishing, urbanization, intensive ... Added to this list in recent years, the global warming that affects a significantly marine biodiversity. Yet the international response to this degradation, beyond the fact that they are shy, is rare. It will therefore fall back on solutions to the global fight against global warming taken by the international community to counter this degradation.